Study in quality of life of women suffering from urinary incontinence - Rezai-Pour; A. Mir-Mowlai; T.Mahmoudi; M. Jabbari Khan Beh Bin; Z (Tehran University of Medical Sciences, 2002)
Urinary incontinence is a common problem in women. It seems to have negative effects on different aspects of the patients' life. This study was undertaken to determine the quality of life in women with urinary incontinence with referred to hospitals affiliated to Tehran University of Medical Sciences. The samples consisted of 263 women all over the age of 18. None of them were pregnant, had not delivered babies last 3 months, had no chronic diseases, were willing to answer questions posed and were also randomly chosen. The samples of the questionnaire about quality of life were collected using I-QOL and variables of type of urinary incontinence, intensity of urinary incontinence, duration of illness, occupation and education were taken into consideration. Analysis of data has been done by using SPSS Statistical tests 2, Pearson and Mantel - Hanzel. Findings of this research indicated that none of the patients led a comfortable life and (45.2%) of them suffered from a quality of life below standard. 51.3% of the women until the time of the study had not visited a physician and 54.8% of them had the impression that the symptoms seemed to be a normal and common problem and that is why they did not seek professional help. The results also indicated that the effect of urinary incontinence was significantly related to the type of urinary incontinence (p<0/0001), duration of the disease (p<0/02) and level of education (p<0/006). In conclusion despite the negative effects of urinary incontinence on the quality of life of women, most of the patients did not seek professional help. It is suggested that the health care providers pay more attention to this issue and utilizing health care centers, train women in the prevention of urinary incontinence.